Single molecule mass photometry of DNA and DNA-protein interactions - Li, Y (2022)
Mass photometry (MP) based on interferometric scattering microscopy (iSCAT) is a novel, label-free imaging and quantification approach, which allows for the accurate mass measurement of biomolecules as well as the quantification of protein-protein interactions in solution. In this work, we show that this approach is equally applicable to DNA and DNA-protein interactions.